Gustav Nikolaus Specht (1860–1940): psychiatric practice, research and teaching during a change of psychiatric paradigm before and after Kraepelin. Issue 2 (June 2022) - Braun, Birgit; Kornhuber, Johannes
Gustav Specht (1860–1940) developed academic psychiatry in Erlangen. After studying medicine in Würzburg, Munich and Berlin, he became assistant medical director in the mental asylum of Erlangen. In 1897 he was appointed extraordinary, and in 1903 ordinary, Professor of Psychiatry. A good clinician and teacher, Specht worked during a time of paradigm change in psychiatry. He was an expert in chronic mania, and introduced the concept of the 'grumbler's delusion'. Paranoia he believed to be the core problem of psychopathology and considered the depressive syndrome as an 'exogenous-type' of reaction. For him, trauma was important in the genesis of mental illness, and his 'hystero-melancholy' anticipated the concept of borderline personality disorder.